2022
DOI: 10.30699/ijp.2022.548036.2833
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Paris 2016 System for Non-invasive Diagnosis Bladder Malignancy

Abstract: Scan to discover onlineBackground & Objective: The Paris System for Reporting Urinary Cytology (TPS) is a new method for evaluating urinary cytology designed to reduce unreproducible reports. The aim of this study was to reclassify and compare urinary cytology reports with TPS criteria to determine the frequency of unreproducible reports compared to the previous system.Methods: In this study, the laboratory electronic registration system analyzed patients' urine samples taken by voided or washing and brushing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our findings further validate that at least five HGCs quantitation requirements per the TPS. More so, the strict application of TPS understandably comes with a low‐to‐moderate sensitivity value (38%–56%) as reported in studies analyzing the impact of TPS, with specificity (97%–100%), PPV (93%–100%), and a NPV as high as 90% 21–24 . We used ThinPrep, and studies have shown that the use of the liquid‐based preparations is reliable, with high ROHM and high concordance among interpreters in detecting HGUC by application of TPS in lower urinary; the rate of detection of HGUC is not affected by the method of specimen collection (voided or collected by bladder washings) 10,20,25,26 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our findings further validate that at least five HGCs quantitation requirements per the TPS. More so, the strict application of TPS understandably comes with a low‐to‐moderate sensitivity value (38%–56%) as reported in studies analyzing the impact of TPS, with specificity (97%–100%), PPV (93%–100%), and a NPV as high as 90% 21–24 . We used ThinPrep, and studies have shown that the use of the liquid‐based preparations is reliable, with high ROHM and high concordance among interpreters in detecting HGUC by application of TPS in lower urinary; the rate of detection of HGUC is not affected by the method of specimen collection (voided or collected by bladder washings) 10,20,25,26 …”
Section: Discussionmentioning
confidence: 98%
“…More so, the strict application of TPS understandably comes with a low-to-moderate sensitivity value (38%-56%) as reported in studies analyzing the impact of TPS, with specificity (97%-100%), PPV (93%-100%), and a NPV as high as 90%. [21][22][23][24] We used ThinPrep, and studies have shown that the use of the liquidbased preparations is reliable, with high ROHM and high concordance among interpreters in detecting HGUC by application of TPS in lower urinary; the rate of detection of HGUC is not affected by the method of specimen collection (voided or collected by bladder washings). 10,20,25,26 Following review of the 36 cases of HGUC (from 22 patients) with negative histology (Cohort 2) on concurrent biopsy, we found all cases meeting the criteria for diagnosing HGUC in lower urinary tract specimens as outlined by TPS.…”
Section: Gendermentioning
confidence: 99%